2008
DOI: 10.1590/s0073-47212008000400015
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive behavior of Leptodactylus mystacinus (Anura, Leptodactylidae) with notes on courtship call of other Leptodactylus species

Abstract: ABSTRACT. Here we present data on the reproductive behavior of Leptodactylus mystacinus (Burmeister, 1861), including details on courtship behavior. We also describe and compared the courtship calls of L. mystacinus, L. furnarius Sazima & Bokermann, 1978 and Leptodactylus sp. (L. aff. andreae). Field works were conducted in Uberlândia (central Brazil). During courtship, a female approaches a calling male and is led to a previously excavated chamber; a female can approach a silent male that beat his hands and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
3
4
0
1
Order By: Relevance
“…Similarly, in an anuran community of southern Brazil, L. mistacynus vocalized for three months, a reproductive pattern intermediate between species active for more than five months and species with only a few nights of activity (Toledo, Zina and Haddad, 2003). Also similar to our observations, in cen-tral Brazil L. mystacinus was active in months of high rainfall, humidity and temperature (de Oliveira Filho and Giaretta, 2008;De-Carvalho et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in an anuran community of southern Brazil, L. mistacynus vocalized for three months, a reproductive pattern intermediate between species active for more than five months and species with only a few nights of activity (Toledo, Zina and Haddad, 2003). Also similar to our observations, in cen-tral Brazil L. mystacinus was active in months of high rainfall, humidity and temperature (de Oliveira Filho and Giaretta, 2008;De-Carvalho et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The advertisement calls of Leptodactylus mystacinus analyzed in this study showed a structure similar to previous descriptions (Barrio, 1965;Oliveira Filho & Giaretta, 2008). We only found differences with the call duration reported by Barrio (1965), of 100 ms; however, suggested that the record of these high values could be due to the methodology employed.…”
Section: Taxonomic Conclusionsupporting
confidence: 87%
“…5B). This behavior was never reported neither for its close relative L. mystacinus (Barrio, 1965;Langone, 1995;Abrunhosa et al, 2001;Oliveira Filho & Giaretta, 2008) nor for any other Leptodactylus species or genus in Leptodactylidae (Lynch 1971;Heyer 1978;de Sá et al, 2014). Reproductive males of L. mystacinus vocalize at shelter under dead logs or rocks, and males of most species in the L. fuscus group usually call from the ground, near or inside underground chambers that they construct for reproduction (Heyer, 1978;de Sá et al, 2014).…”
Section: Taxonomic Conclusionmentioning
confidence: 89%
“…Nevertheless, the observations of the incubation chamber construction are quite rare and lacking for most of the species of the group. Reports about which sex excavates the burrow exist for Leptodactylus bufonius (Cei 1949; Reading and Jofré 2003), Leptodactylus mystacinus (Oliveira Filho and Giaretta 2008), L. fuscus (Cei 1949; Martins 1988; Giaretta and Kokubum 2004), Leptodactylus mystaceus (Caldwell and Lopez 1989), and L. latinasus (Gallardo 1958, 1964) . If we had found sexual dimorphism in the nasal capsules or head dimensions of L. latinasus , then the relationship of these characters with the construction of the incubation chamber might have been used to predict that sex is involved in this behavior for species in the group for which there are not behavioral observations.…”
Section: Discussionmentioning
confidence: 99%